Enhancing customer service through prompt service delivery: the case of the Forest Services Division in the Northern Region - Djagbletey, Ebenezer Djaney (2012)
A Thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters of Business Administration,